Low-temperature sintering and piezoelectric properties of CuO-doped (K, Na)NbO3 ceramics. (December 2017) - Kim, J.H.; Kim, J.S.; Han, S.H.; Kang, H.-W.; Lee, H.-G.; Cheon, C.I.
Graphical abstract: Highlights: KNN-based lead-freepiezoelectric ceramics was fabricated at the sintering temperature below 950 °C by co-doping with Na2 CO3 and CuO for multilayered piezoelectric devices. The co-doped sample has not only a high mechanical quality factor (Qm ) over 900 but also excellent piezoelectric properties. Mechanisms on micostructure development and the change in piezoelectric properties with the sintering temperature were proposed. Abstract: The lead-free piezoelectric [(K0.485 Na0.515 )0.935 Li0.065 ](Nb0.99 Ta0.01 )O3 (KNLNT) ceramics with a high mechanical quality factor (Qm ) were prepared at low sintering temperature below 950 °C for multilayered piezoelectric devices. Co-doping effect of 1 mol% Na2 CO3 and 0–1 mol% CuO on the densification and piezoelectric properties were investigated. Co-doping effectively decreased the sintering temperature of KNLNT ceramics to 920 °C. The co-doped KNLNT ceramics had a bimodal size distribution of large abnormal grains and small matrix grains above 900 °C. When the sintering temperature increased above 900 °C, a dielectric constant (εr ) and loss (tan δ) decreased considerably and concurrently mechanical quality factor (Qm ) greatly enhanced. The co-doped KNLNT ceramic with 1 mol% Na2 CO3 and 0.5 mol% CuO had a high Qm and excellent piezoelectric properties when sintered at 940 °C: a dielectric constant of 245 and loss (tan δ) of 0.0034, an electromechanical coupling factor ( k p ) of 0.449, and Qm of 904.